2020
DOI: 10.1016/j.jadohealth.2020.03.007
|View full text |Cite
|
Sign up to set email alerts
|

School Satisfaction and School Pressure in the WHO European Region and North America: An Analysis of Time Trends (2002–2018) and Patterns of Co-occurrence in 32 Countries

Abstract: The purpose of the study was to examine the trends between 2002 and 2018 in school pressure and school satisfaction among 15-year-old students, across countries and by gender, in the WHO European region and North America, and explore whether there are variations between countries and by gender in the co-occurrence of school pressure and school satisfaction. Methods: Data from the 32 countries that participated in the Health Behaviour in School-aged Children study (HBSC) study between 2002 and 2018 were used. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 35 publications
(31 reference statements)
1
36
0
1
Order By: Relevance
“…The reduced academic load during home schooling likely necessitated increased study once schools reopened to make up for the lost months and allow them to complete entire semester courses before mid-July, potentially resulting in excessive homework and restrictions on extra-curricular recreational activities. Previous studies have demonstrated that academic pressure was the most commonly identified stressor across students, irrespective of age and sex, which was largely driven by parental and teacher expectations 30 , 31 . Indeed, during this special period of school reopening, the sudden shift to strict, organized in-person schooling and the stark discrepancy between home and school environments may have created new psychological stressors for families, as demonstrated by the increase in parent-child conflict documented in the RS group.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced academic load during home schooling likely necessitated increased study once schools reopened to make up for the lost months and allow them to complete entire semester courses before mid-July, potentially resulting in excessive homework and restrictions on extra-curricular recreational activities. Previous studies have demonstrated that academic pressure was the most commonly identified stressor across students, irrespective of age and sex, which was largely driven by parental and teacher expectations 30 , 31 . Indeed, during this special period of school reopening, the sudden shift to strict, organized in-person schooling and the stark discrepancy between home and school environments may have created new psychological stressors for families, as demonstrated by the increase in parent-child conflict documented in the RS group.…”
Section: Discussionmentioning
confidence: 99%
“…Research on mindfulness suggests that females, both adults and adolescents, in general benefit more from mindfulness interventions, especially in terms of psychological well-being [12,13,27]. As the academic pressure and social media use place increasing demands to students mental health [28]; [31], school-based mindfulness programs teach directing attention and encourage acceptance toward emerging emotions [21], higher self-compassion, and self-acceptance [4,7,24]. For adolescents, mindfulness practice may also lessen the detrimental self-focus in challenging situations [5] and support adaptive development [2].…”
Section: Mindfulness Practice and Its Moderatorsmentioning
confidence: 99%
“…The small decline in mental health and well-being and increases in schoolwork pressure appears to be consistent with high-income countries. Löfstedt et al, using HBSC data across five cohorts (2002e2018) from 32 countries, further increases our understanding of the school satisfaction and school pressure by gender [7]. In the final analyses, boys appear to be more satisfied with school over time, whereas girls appear to feel more pressured by school.…”
Section: Mental Health and Well-beingmentioning
confidence: 96%